Patient‐Reported Social Determinants of Health in Patients With Heart Failure - Kenneth E. Freedland; Brian C. Steinmeyer; Judith A. Skala; Robert M. Carney; Michael W. Rich (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Social determinants of health (SDOH) complicate medical care and affect clinical outcomes, but the lack of a reliable structured interview for medical patients has impeded clinical assessment and research on SDOH. We assessed the reliability and validity of a newly developed SDOH Patient Interview Form and investigated SDOH in patients with heart failure. Methods The SDOH Patient Interview Form was administered to recently hospitalized patients with heart failure between January 2021 and April 2024. The interviews were recorded, and 50 were randomly selected for the interrater reliability analysis. Results The sample included 367 participants (mean age, 61.2±12.1 years; 42.5% women; 57.7% minorities). The interrater reliability of SDOH Patient Interview Form categories (eg, Legal and Social Problems) was 100%. The κ reliability coefficients for individual items were ≥0.94. Higher lifetime SDOH counts were associated with lower age and income and higher New York Heart Association class and body mass index. Two distinct sets of problems were found to contribute to relatively high burdens of SDOH. The first originates with abuse in childhood and presents as severe socioeconomic deprivation in adulthood. The second includes losses of family members and occupational, financial, and caregiver stress along with difficulty affording medical care. Conclusions The SDOH Patient Interview Form is a reliable instrument for assessing patient‐reported SDOH in patients with heart failure. It is suitable for use in research and clinical contexts but requires further testing in other medical patient populations. This study revealed 2 distinct patterns of stressful problems that can contribute to a high overall burden of SDOH. Registration URL: https://clinicaltrials.gov; Unique identifier: NCT04637776.